Health behaviours as the essential health factor - Tiszczenko, Ewgenij M.; Surmach, Marina J.; Piecewicz-Szczęsna, Halina (Polish Journal of Public Health, 2009)
Health is a phenomenon depending on multiple factors. Until recently, the system of health care has been considered in Belarus the main factor responsible for public health state. It was supported by the tradition of collectivism and allowed avoiding individual responsibility. The aim of the work was to present selected environmental, demographic, health as well as social features of Byelorussian society as factors motivating people to change health behaviours.At the same time, during social transformations and recent economic crisis, changes in health condition of population in Belarus have been observed. They lead to depopulation, and increase of chronical pathologies (for the last ten years the level of incidence rate in Belarus has grown by 5.3%, and the level of prevalence rate – by 16.3%).  The prevalence rate of diseases caused by psycho-social factors have shown a surge (from 1995 the proportion of pe ople suffering from chronical alcoholism and mental alcohol disorders has increased by 56.5%; the number of children below 15 years of age, suffering from drug abuse, increased more than 6 times; the prevalence rate of cardiovascular diseases raised by 75.2%). People rarely refer for medical consultations and more often demonstrate improper forms of behaviour regarding their own health. All factors listed above made it indispensible to reconsider social priorities and to recognise the key role of a person in the public health issue.A series of actions have been taken up in national programme to strengthen and support the health of society: the year 2006 was proclaimed The Health Promotion Year, 2007 – The Mother’s Health Year, 2008 is a Year of Health. Modern tendencies show shift of accents: from desease towards health, from medical treatment to prevention, from patient to person, from therapy to care, from medical institution to society.